Positive electrode material, preparation method thereof, positive electrode plate and sodium ion battery
By optimizing the molar ratio of olivine phosphate and polyanionic phosphate and designing composite particle structure, combined with carbon layer coating, the problem of poor electrical performance of the positive electrode material of sodium ion battery is solved, significantly improving capacity and electrochemical performance .
Patent Information
- Application Number
- CN202411541358.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-31
AI Technical Summary
The electrical performance of existing sodium ion battery positive electrode materials is poor, especially the olivine type NaFePO4 and pyrophosphate Na2FeP2O7 are insufficient in terms of operating voltage and reversible capacity, and the prior art has failed to effectively achieve synergy between different crystal phases. effect.
By optimizing the molar ratio of olivine phosphate to polyanionic phosphate in iron-based composite phosphate materials (0.2~0.5:1), the composite particle structure is designed so that the polyanionic phosphate is wrapped in olivine phosphate. Achieve nanocrystalline and two-phase interface penetration, improve electrochemical activation, and coat the material surface with carbon layers to improve conductivity and structural stability.
The capacity and electrochemical properties of the cathode material are significantly improved, so that the sodium ion battery exhibits higher energy density, cycle stability and charge and discharge efficiency.
Smart Images

Figure CN119230795A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a positive electrode material, a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art
[0002] In recent years, a lot of effort has been put into developing cost-effective and high-performance cathode materials to realize commercially available sodium-ion batteries (e.g., in the field of new energy vehicles, etc.). In the similar field of lithium-ion batteries, the LiFePO4 cathode has achieved great commercial success in lithium-ion batteries. This type of iron-based phosphate material has good performance and is cheap, so it is considered to be one of the best choices for cathode active materials in secondary batteries.
[0003] However, the thermodynamic properties of olivine NaFePO4 (NFP) are not good and it is considered to be electrochemically inert. In contrast, pyrophosphate Na2FeP2O7 materials, due to their open three-dimensional Na + Channel, while P2O7 in its crystal 4- The material has a strong inductive effect, so it allows a higher operating voltage (~3.0V), but the low reversible capacity of Na2FeP2O7 (<100mAh·g -1 ) seriously hinders its practical application.
[0004] Whether it is olivine phosphate or polyanion phosphate, both have certain shortcomings when used as positive electrode active materials for sodium ion batteries, and their corresponding battery performance is therefore lacking. At present, the existing technology provides a polyanion positive electrode material including phosphate and a carbon layer coated on the surface of the phosphate, wherein the phosphate includes NFPP, NFP and NNFPO, and the content ratio of NFP and NNFPO is controlled by multiple short-time sintering. However, the technical solution provided by it only reduces the impurity phase in the positive electrode material, and does not achieve the synergistic effect between different crystal phases, so the performance of the obtained positive electrode material still needs to be improved.
[0005] Based on this, how to design the positive electrode active material of the sodium ion battery at the crystal phase level so that it has better electrochemical performance is one of the important technical problems that need to be solved in this field. Summary of the invention
[0006] The main purpose of the present invention is to provide a positive electrode material, a preparation method thereof, a positive electrode plate and a sodium ion battery, so as to solve the problem of poor electrical performance of the positive electrode material of the sodium ion battery in the prior art.
[0007] In order to achieve the above object, the first aspect of the present invention provides a positive electrode material, the positive electrode material includes composite particles, the molecular formula of the composite particles is: Na x Fe y (PO4) n (P2O7) m , x is 4.2 to 4.5, y is 3.2 to 3.5, n is 2.2 to 2.5, and m is 0.9 to 1.1; the composite particles include olivine phosphate (NaFePO4, NFP) and polyanionic phosphate (Na4Fe3(PO4)2P2O7, i.e. NFPP) coated on the surface of the olivine phosphate, and the molar ratio of the olivine phosphate to the polyanionic phosphate is (0.2 to 0.5):1.
[0008] The present invention optimizes the positive electrode material, that is, in the iron-based composite phosphate material, the molar ratio of olivine phosphate to polyanionic phosphate is (0.2-0.5):1, and the microstructure of the composite particles formed by the two is designed, so that the polyanionic phosphate phase wraps the olivine phosphate crystal, realizes nanocrystallization and two-phase interface penetration at the crystal structure level, and can induce Na + Through the olivine-type phosphate phase, the electrochemical activation of the olivine-type phosphate phase is achieved, thereby significantly improving the capacity of the iron-based composite phosphate (NxFPP).
[0009] Furthermore, the molar ratio of olivine phosphate to polyanionic phosphate is (0.2-0.4):1. When the proportion of olivine phosphate in the material structure is too high, it is difficult for the polyanionic phosphate crystal phase to completely wrap the olivine phosphate crystal, resulting in the presence of olivine phosphate crystals formed alone outside the polyanionic phosphate crystals, which become the impurity phase in the polyanionic phosphate crystals, resulting in a lower capacity of the composite material. When the proportion of olivine phosphate is too low, the olivine phosphate crystals inside the polyanionic phosphate crystals are correspondingly less, making it difficult to fully penetrate the two-phase interface, and the electrochemically activated olivine phosphate phase is less, making it difficult to significantly increase the capacity of the composite material.
[0010] Furthermore, in order to improve the conductivity of the obtained positive electrode material and the structural stability during the charge-discharge process, the positive electrode material also includes a carbon layer coated on the surface of the composite particles, and the mass fraction of the carbon layer is 1.5% to 3.0% based on the total weight of the positive electrode material as 100%.
[0011] Regarding the coated carbon layer, the mass fraction is preferably as above, so as to form a more complete carbon coating layer, improve the electronic conductivity of the positive electrode material, thereby reducing its powder internal resistance and improving its electrochemical performance. Preferably, the carbon layer is an amorphous carbon part formed by an organic carbon source and / or an inorganic carbon part formed by an inorganic carbon source.
[0012] More preferably, the carbon layer is a combination of an amorphous carbon portion and an inorganic carbon portion, and based on the total weight of the carbon layer being 100%, the weight of the inorganic carbon portion accounts for 2.5% to 5.0%.
[0013] The positive electrode material provided by the present invention preferably contains an amorphous carbon portion formed by an organic carbon source and an inorganic carbon portion formed by an inorganic carbon source in the carbon layer coated on the outermost layer. The amorphous carbon portion is formed by uniformly coating the composite particles with a soluble organic carbon source after calcination, and the inorganic carbon portion is interspersed in the amorphous carbon portion to form a good and uniform carbon coating. The amorphous carbon portion has a higher specific surface area and better mechanical properties, and the inorganic carbon portion with a higher degree of graphitization can provide better electronic conductivity. The two work together to further improve the electrochemical properties of the positive electrode material.
[0014] Furthermore, the powder resistivity of the positive electrode material is 12000 Ω·cm to 93000 Ω·cm. The positive electrode material obtained by the present invention has a lower resistivity, and when used as a positive electrode active material of a sodium ion battery, the corresponding battery can exhibit a higher charge specific capacity and discharge specific capacity.
[0015] The second aspect of the present invention provides a method for preparing a positive electrode material, comprising: preparing a sodium source, an iron source and a phosphorus source into a first slurry; subjecting the first slurry to a first drying and a first calcination to obtain a precursor; preparing the precursor and a carbon source into a second slurry; and subjecting the second slurry to a second drying and a second calcination to obtain a positive electrode material.
[0016] In the preparation process provided by the present invention, a two-step process is adopted, that is, a sodium source, an iron source and a phosphorus source are first prepared to obtain a precursor, and then a carbon source and the precursor are formed into a uniform slurry. After the second drying and the second calcination, the carbon source is uniformly coated on the outside of the pure phase grains of the precursor to obtain a positive electrode material with low powder resistivity, which helps to improve the electronic conductivity and capacity of the obtained positive electrode material. At the same time, in the preparation process, the pure phase of the precursor obtained after the first drying and the first calcination has formed grains of a certain size, and the secondary coating of carbon will not affect its grain structure. The above two-step preparation process is conducive to obtaining the above-mentioned positive electrode material with a coating structure provided by the present invention, and improving the compaction density and tap density of the obtained positive electrode material.
[0017] In some embodiments, in the first slurry, the molar ratio of the sodium source, the iron source, and the phosphorus source is (4.2-4.86): (3.2-3.5): (4.2-4.5). In this addition amount relationship, compared with the final composite particles, the sodium source is in excess, which is beneficial to avoid Na loss during high-temperature sintering and obtain composite particles with more complete crystal forms.
[0018] Further, in order to make the precursor crystal phase obtained by the first calcination higher in purity, have better structural stability and ion diffusion performance, and ultimately show higher energy density in sodium ion batteries, preferably, the first calcination includes a first calcination and a second calcination performed in sequence, wherein the temperature of the first calcination is 400°C to 500°C, and the time is 1.5h to 2.5h; the temperature of the second calcination is 550°C to 650°C, and the time is 10h to 14h. Through the above calcination method and the setting of temperature and time parameters, it is conducive to the sequential formation of olivine phosphate and polyanionic phosphate, and is conducive to the formation of composite particles of polyanionic phosphate coated on the surface of olivine phosphate, and is conducive to better compounding between the two crystal phases, thereby significantly improving the electrochemical performance of the obtained positive electrode material. At the same time, in order to reduce the introduction of impurities, it is more preferred that the first calcination is carried out under a protective atmosphere to obtain a positive electrode material with higher electrochemical performance.
[0019] Preferably, the sodium source is selected from one or more of sodium bicarbonate, sodium phosphate, sodium monohydrogen phosphate and sodium dihydrogen phosphate; the iron source is selected from one or more of anhydrous ferric phosphate, polyhydrated ferric phosphate, ferrous phosphate monohydrogen and ferrous oxalate; the phosphorus source is selected from one or more of anhydrous ferric phosphate, diammonium phosphate, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, polyhydrated ferric phosphate and ferrous oxalate.
[0020] Furthermore, the carbon source includes an organic carbon source and / or an inorganic carbon source, preferably the organic carbon source is selected from one or more of citric acid, glucose, sucrose, soluble starch and polyethylene glycol; and / or the inorganic carbon source is selected from one or more of graphite, carbon nanotubes and graphene. The above carbon source can undergo a more complete graphitization reaction during the second calcination process, and the coating degree is more uniform, thereby more significantly optimizing the electrochemical performance of the obtained positive electrode material.
[0021] Preferably, the carbon source includes soluble starch, polyethylene glycol and graphene; more preferably, the polyethylene glycol is PEG-2000; more preferably, in the carbon source, the ratio of the addition amount of soluble starch, PEG-2000 and graphene is (1.2-1.5):1:(0.2-0.4). The inventors have optimized the types of carbon sources used through a large number of experiments to obtain the above-mentioned carbon source combination, wherein the amorphous carbon layer formed after sintering of soluble starch has a higher porosity, but a lower powder resistivity; the carbon layer formed after sintering of PEG-2000 is more compact, and the composite use of the two helps to increase the compaction density of the material, reduce the powder resistivity of the material, and ultimately improve the electrochemical performance of the obtained positive electrode material in sodium ion batteries; at the same time, graphene has a unique sheet structure (two-dimensional structure), which is conducive to coating on the surface of the precursor and forming point-surface contact with the precursor. At the same time, the compound use of soluble starch, PEG-2000 and graphene helps to reduce the BET specific surface area of the positive electrode material, reduce the water absorption of the obtained positive electrode material, and improve the processing performance of the positive electrode material. Considering the inevitable losses in the subsequent calcination process and the coordination of the three, the compound use of the three in the above-mentioned dosage relationship is conducive to better synergizing the superior performance of graphene, polyethylene glycol and soluble starch after calcination, thereby obtaining a uniformly coated carbon layer with good conductivity, and improving the electrochemical performance of the obtained positive electrode material.
[0022] Furthermore, the second calcination includes the following steps in sequence: a first calcination at a temperature of 40°C to 60°C and a holding time of 1h to 2h; a second calcination at a temperature of 100°C to 130°C and a holding time of 0.5h to 1.5h; a third calcination at a temperature of 180°C to 210°C and a holding time of 2h to 4h; and a fourth calcination at a temperature of 500°C to 600°C and a holding time of 2h to 6h.
[0023] The present invention optimizes the specific steps in the second calcination into four stages of calcination performed sequentially, which helps to achieve the segmented decomposition of the carbon source mixed with the precursor, avoiding its large-scale decomposition in a certain temperature range, generating more gas, and a large amount of other escapes causing the material volume to expand significantly, resulting in a decrease in the filling rate and a decrease in electrochemical performance. In addition, the segmented calcination makes the gas escape more slowly, better avoiding the reduction of the compacted density, the increase of the BET specific surface area, the deterioration of the electrochemical performance, etc. caused by the rapid contraction of a large number of void structures formed in the obtained positive electrode material first.
[0024] Furthermore, the heating rates of the first calcination, the second calcination, the third calcination, and the fourth calcination are independently 3°C / min to 10°C / min. The heating rate can better adapt to the state of the composite material corresponding to the above four calcination processes, so as to obtain a positive electrode material with excellent phase purity and crystallinity, improve its performance in sodium ion batteries, and ultimately optimize the capacity of the resulting battery.
[0025] The third aspect of the present invention provides a positive electrode sheet, which includes the above-mentioned positive electrode material, or includes the positive electrode material prepared by the preparation method of the above-mentioned positive electrode material. The above-mentioned positive electrode material or the obtained above-mentioned positive electrode material has a lower powder resistivity, so that the positive electrode sheet in which it is located can have better comprehensive performance.
[0026] The fourth aspect of the present invention provides a sodium ion battery, which includes the above-mentioned positive electrode plate. Since the positive electrode material in the positive electrode plate obtained by the present invention has excellent performance, the sodium ion battery in which it is located exhibits higher energy density, higher capacity and efficiency, and also has excellent cycle stability.
[0027] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 This is the SEM result of the positive electrode material obtained in Example 1;
[0030] Figure 2 This is the SEM result of the positive electrode material obtained in Example 14;
[0031] Figure 3 This is the SEM result of the positive electrode material obtained in Example 15;
[0032] Figure 4 This is a process flow chart of the method for preparing the positive electrode material provided in the embodiment. DETAILED DESCRIPTION
[0033] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0035] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0037] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0038] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0039] As described in the background art, the sodium ion battery positive electrode material in the prior art has the problem of poor electrical performance. In order to solve the above technical problems, the first aspect of the present invention provides a positive electrode material, which includes composite particles, and the molecular formula of the composite particles is: Na x Fe y (PO4) n (P2O7) m, x is 4.2 to 4.5, y is 3.2 to 3.5, n is 2.2 to 2.5, and m is 0.9 to 1.1; the composite particles include olivine phosphate (NaFePO4, NFP) and polyanionic phosphate (Na4Fe3(PO4)2P2O7, i.e. NFPP) coated on the surface of the olivine phosphate, and the molar ratio of the olivine phosphate to the polyanionic phosphate is (0.2 to 0.5):1.
[0040] In some embodiments, the composite particles have a molecular formula of Na x Fe y (PO4) n (P2O7) m , x is 4.2, 4.3, 4.4, or 4.5; y is 3.2, 3.3, 3.4, or 3.5; n is 2.2, 2.3, 2.4, or 2.5; and m is 0.9 or 1.0.
[0041] The present invention optimizes the positive electrode material, that is, the molar ratio of olivine phosphate to polyanionic phosphate in the iron-based composite phosphate material is (0.2-0.5):1, and designs the microstructure of the composite particles formed by the two, so that the polyanionic phosphate phase wraps the nanocrystal of olivine phosphate, realizes nanocrystalization at the crystal structure level and two-phase interface penetration, and can induce Na + Through the olivine phosphate phase, the electrochemical activation of the olivine phosphate phase is achieved, and the capacity of the iron-based composite phosphate (precursor, NxFPP) is significantly improved. Specifically, due to the higher electrochemical performance of the polyanionic phosphate, especially in terms of theoretical specific capacity, voltage platform and cycle stability, by coating it outside the olivine phosphate, the overall electrochemical performance of the obtained material can be significantly improved, so that after it is used as a positive electrode material to prepare a sodium ion battery, the battery performs better during the charge and discharge process.
[0042] In addition, in terms of structural stability, the coating of the polyanionic phosphate phase provides additional structural support for the olivine phosphate phase, reducing the structural damage during the charge-discharge process, thereby enhancing the cyclic stability of the material. At the same time, the coating of the polyanionic phosphate improves the Na + The ion diffusion path makes the diffusion smoother, thereby improving the charging and discharging rates of the battery. In addition, this encapsulated structure can also reduce the side reaction between the olivine phosphate and the electrolyte, thereby extending the service life of the battery.
[0043] Furthermore, taking into account the different electrochemical properties, cycle stability, ion diffusion efficiency and synthesis process cost of the polyanionic phosphate phase and the olivine phosphate phase, the present invention strictly controls the molar ratio of olivine phosphate to polyanionic phosphate to be (0.2-0.5):1, so as to achieve complete coating of the polyanionic phosphate phase on the surface of the olivine phosphate phase, avoiding unsatisfactory capacity enhancement due to the formation of impurities or the inability to achieve penetration at the interface between the two phases.
[0044] In other words, the positive electrode material with the above structure provided by the present invention shows significant advantages in terms of energy density, electrochemical performance, structural stability and safety.
[0045] Furthermore, the molar ratio of olivine phosphate to polyanionic phosphate is (0.2-0.4):1. The inventors further adjusted the molar ratio of olivine phosphate to polyanionic phosphate through a large number of experiments and creative work, and optimized this value to (0.2-0.4):1. This is because when the proportion of olivine phosphate in the material structure is too high, the polyanionic phosphate crystal phase is difficult to completely encapsulate the olivine phosphate nanocrystalline phase, and the olivine phosphate forms crystals alone and is distributed outside the polyanionic phosphate crystals, becoming a miscellaneous phase in the polyanionic phosphate crystals, resulting in a lower capacity of the composite material. When the proportion of olivine phosphate is too low, the olivine phosphate nanocrystalline phase inside the polyanionic phosphate crystal phase is correspondingly less, and it is difficult to form sufficient two-phase interface penetration, and the electrochemically activated olivine phosphate phase is less, so that the capacity of the composite material cannot be significantly improved.
[0046] It is necessary to explain that in practical applications, for the positive electrode material provided by the present invention, there is an inevitable loss of P and PO4 during the sintering process during its preparation process. 3- Transformed into P2O7 4- Due to the uncertainty of the above, the relationship between the molecular formula of the composite particles and the molar ratio of the olivine phosphate and the polyanionic phosphate may not correspond completely, but the above relationship corresponds within the detection limit.
[0047] Specifically, the composite particle formula is Na 4.2 Fe 3.2 (PO4) 2.2 P2O7, at this time, the molar ratio of olivine phosphate to polyanionic phosphate is 0.2:1; or the molecular formula of the composite particle is Na 4.3 Fe 3.3 (PO4) 2.3 P2O7, the molar ratio of olivine phosphate to polyanionic phosphate is 0.3:1; or the molecular formula of the composite particle is Na4.4 Fe 3.4 (PO4) 2.4 P2O7, at this time, the molar ratio of olivine phosphate to polyanionic phosphate is 0.4:1; or the molecular formula of the composite particle is Na 4.5 Fe 3.5 (PO4) 2.5 P2O7, at this time the molar ratio of olivine phosphate to polyanion phosphate is 0.5:1.
[0048] Further, in order to improve the conductivity of the obtained positive electrode material and the structural stability during the charge and discharge process, the positive electrode material also includes a carbon layer coated on the surface of the composite particles, and the mass fraction of the carbon layer is 1.5% to 3.0%, such as 1.5%, 2.0%, 2.5%, and 3.0%, based on the total weight of the positive electrode material as 100%. Regarding the coated carbon layer, the mass fraction is preferably as above, so as to form a more complete carbon coating layer while not excessively increasing the resistance to sodium ion transmission, thereby improving its electrochemical performance. Preferably, the carbon layer is an amorphous carbon part formed by an organic carbon source and / or an inorganic carbon part formed by an inorganic carbon source; more preferably, the carbon layer is a combination of an amorphous carbon part and an inorganic carbon part, and the weight of the inorganic carbon part accounts for 2.5% to 5.0%, such as 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, and 5.0%, based on the total weight of the carbon layer as 100%. The positive electrode material provided by the present invention preferably contains an amorphous carbon portion formed by an organic carbon source and an inorganic carbon portion formed by an inorganic carbon source in the carbon layer coated on the outermost layer. The amorphous carbon portion is formed by uniformly coating the composite particles with a soluble organic carbon source after calcination, and the inorganic carbon portion is interspersed in the amorphous carbon portion to form a good and uniform carbon coating. The amorphous carbon portion has a higher specific surface area and better mechanical properties, and the inorganic carbon portion with a higher degree of graphitization can provide better electronic conductivity. The two work together to further improve the electrochemical properties of the positive electrode material.
[0049] Further, the powder resistivity of the positive electrode material is 12000Ω·cm~93000Ω·cm, preferably 17000Ω·cm~33000Ω·cm, such as 17050Ω·cm, 17600Ω·cm, 18400Ω·cm, 18900Ω·cm, 19900Ω·cm and 32070Ω·cm; the tap density is 0.9g / mL~1.2g / mL, preferably 1.14g / mL~1.19g / mL, such as 1.14g / mL, 1.17g / mL, 1.18g / mL, 1.19g / mL; the compaction density is 1.7g / cm 3 ~2.2g / cm 3 , preferably 1.95 g / cm 3 ~2.18g / cm 3, for example 1.98g / cm 3 , 2.08g / cm 3 , 2.12g / cm 3 , 2.13g / cm 3 , 2.15g / cm 3 , 2.16g / cm 3 ; The filling rate is 60.0% to 76.5%, preferably 72.3% to 76.1%, such as 72.30%, 75.01%, 75.38%, 75.47%, 76.00%, 76.03%; The specific surface area is 9m 2 / g~50m 2 / g, preferably 11.5m 2 / g~35.7m 2 / , for example 11.71m 2 / g, 12.00m 2 / g, 12.30m 2 / g, 12.85m 2 / g, 14.63m 2 / g, 35.67m 2 / g. The positive electrode material obtained by the present invention has a higher compaction density, a lower specific surface area, and especially a smaller resistivity. When used as a positive electrode active material for a sodium ion battery, the corresponding battery can exhibit a higher charge specific capacity and discharge specific capacity.
[0050] The second aspect of the present invention provides a method for preparing a positive electrode material, comprising: preparing a sodium source, an iron source and a phosphorus source into a first slurry; subjecting the first slurry to a first drying and a first calcination to obtain a precursor; preparing the precursor and a carbon source into a second slurry; and subjecting the second slurry to a second drying and a second calcination to obtain a positive electrode material.
[0051] In the preparation process provided by the present invention, a two-step process is adopted, that is, a sodium source, an iron source and a phosphorus source are first prepared to obtain a precursor, which is a complex of an olivine-type phosphate and a polyanionic phosphate, and then a carbon source and a precursor are formed into a uniform slurry, and after a second drying and a second calcination, the carbon source is uniformly coated on the outside of the pure phase grains of the precursor to obtain a positive electrode material with low powder resistivity, which helps to improve the electronic conductivity of the obtained positive electrode material. Therefore, the positive electrode material prepared by this method, that is, the NxFPP / C composite material has a higher capacity. At the same time, during the preparation process, the pure phase of the precursor obtained after the first drying and the first calcination has formed grains of a certain size, and the secondary coating of carbon will not affect the grain structure of the precursor. The above two-step preparation process is conducive to obtaining the above-mentioned positive electrode material with a coating structure provided by the present invention, and improving the compaction density and tap density of the obtained positive electrode material.
[0052] In the one-step preparation process commonly used in the art, except for the insoluble iron source and part of the carbon source in the slurry, the other raw materials are soluble in water to form a uniform slurry, and the water evaporates quickly during drying, and the soluble sodium salt, phosphate salt, and carbon source are mixed and coated on the outside of the insoluble iron source and part of the carbon source. The carbon layer formed by the carbon source during the sintering process is mixed in the middle of the mixture, which hinders the migration and fusion of other ions to a certain extent. At the same time, due to the growth and fusion of the precursor grains, the carbon layer cannot be uniformly coated on the outside of the precursor grains, and the powder resistivity is high. In addition, the carbon source is mixed in the inorganic phase, which hinders the growth of the precursor grains to a certain extent, and the carbon source volatilizes during the sintering process, leaving a structure with more pores, and the smaller precursor grains are embedded in it and cannot form effective filling and support, resulting in a low compaction density and tap density of the composite material formed by the one-step method.
[0053] It is necessary to explain that, in practical applications, for the positive electrode material provided by the present invention, there is an inevitable loss of P and PO4 during the sintering process during its preparation process. 3- Transformed into P2O7 4- Due to the uncertainty of the above, the relationship between the molecular formula of the composite particles and the molar ratio of the olivine phosphate and the polyanionic phosphate may not correspond completely, but the above relationship corresponds within the detection limit.
[0054] In some embodiments, in the first slurry, the molar ratio of the sodium source, the iron source and the phosphorus source is (4.2-4.86): (3.2-3.5): (4.2-4.5), such as 4.2:3.2:4.2, 4.5:3.3:4.2, 4.8:3.2:4.5. In this addition amount relationship, compared with the final composite particles, the sodium source is partially excessive, and the mass fraction of the excess sodium source is preferably 5.0% to 5.5%, such as 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, because the inventors have conducted a large number of experiments and found that it is beneficial to avoid Na loss during high-temperature sintering and obtain core composite particles with more complete crystal forms.
[0055] Further, in order to make the precursor obtained by the first calcination have a higher crystal phase purity, better structural stability and ion diffusion performance, and finally show a higher energy density in the sodium ion battery, preferably, the first calcination includes a first calcination and a second calcination performed in sequence, wherein the temperature of the first calcination is 400°C to 500°C, such as 440°C, 450°C, 460°C, and the time is 1.5h to 2.5h; the temperature of the second calcination is 550°C to 650°C, such as 580°C, 600°C, 620°C, and the time is 10h to 14h, such as 11h, 12h, 13h. Through the above calcination method and the setting of temperature and time parameters, it is conducive to the sequential formation of olivine phosphate and polyanionic phosphate, to the formation of composite particles of polyanionic phosphate coated on the surface of olivine phosphate, and to better compound between the two crystal phases, thereby significantly improving the electrochemical performance of the obtained positive electrode material. At the same time, in order to reduce the introduction of impurities, it is more preferred that the first calcination be performed under a protective atmosphere to obtain a positive electrode material with higher electrochemical performance.
[0056] Furthermore, the carbon source includes an organic carbon source and / or an inorganic carbon source. Furthermore, the inventors have optimized the type of carbon source through a large number of experiments and found that when the organic carbon source is selected from one or more of citric acid, glucose, sucrose, soluble starch and polyethylene glycol; and / or the inorganic carbon source is selected from one or more of graphite, carbon nanotubes and graphene, the above-mentioned carbon source can undergo a more sufficient graphitization reaction in the second calcination process, and the coating degree is more uniform, thereby more significantly optimizing the electrochemical performance of the obtained positive electrode material.
[0057] In several typical embodiments, the preferred carbon source includes soluble starch, polyethylene glycol and graphene; more preferably, the polyethylene glycol is PEG-2000; more preferably, in the carbon source, the ratio of the added amount of soluble starch, PEG-2000 and graphene is (1.2-1.5):1:(0.2-0.4) such as 1.24:1:0.4, 1.4:1:0.2, 1.48:1:0.2, preferably (1.25-1.5):1:(0.2-0.3). The inventors have obtained the above carbon source combination through a large number of experiments to optimize the types of carbon sources used. Among them, the amorphous carbon layer formed after sintering of soluble starch has a higher porosity, but a lower powder resistivity; the carbon layer formed after sintering of PEG-2000 is more dense, and the composite use of the two helps to increase the compaction density of the material, reduce the powder resistivity of the material, and ultimately improve the electrochemical performance of the obtained positive electrode material in sodium ion batteries; at the same time, graphene has a unique sheet structure (two-dimensional structure), which is conducive to coating on the surface of NxFPP and forming point-surface contact with NxFPP. At the same time, the composite use of soluble starch, PEG-2000, and graphene helps to reduce the BET specific surface area of the positive electrode material, reduce the water absorption of the obtained positive electrode material, and improve the processing performance of the material. Considering the inevitable losses in the subsequent calcination process and the coordination of the three, the three are compounded and used in the above-mentioned dosage relationship, which is conducive to better synergizing the superior performance of graphene, polyethylene glycol and soluble starch after calcination, thereby obtaining a uniformly coated carbon layer with good conductivity, and improving the electrochemical performance of the obtained positive electrode material. At the same time, if too much graphene is added, not only will the capacity and powder resistivity of the material not be significantly improved, on the contrary, graphene is expensive, and excessive addition will lead to higher production costs of the composite material, which is not conducive to the low-cost advantage of sodium-ion batteries.
[0058] Specifically, the sodium source used in the present invention is selected from one or more of sodium bicarbonate, sodium phosphate, sodium monohydrogen phosphate and sodium dihydrogen phosphate; the iron source is selected from one or more of anhydrous ferric phosphate, polyhydrated ferric phosphate, ferrous phosphate monohydrogen and ferrous oxalate; the phosphorus source is one or more of anhydrous ferric phosphate, diammonium phosphate, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, polyhydrated ferric phosphate and ferrous oxalate.
[0059] Furthermore, the second calcination includes the following steps: a first calcination at a temperature of 40°C to 60°C, such as 45°C, 50°C, and 55°C, and a holding time of 1h to 2h; a second calcination at a temperature of 100°C to 130°C, such as 110°C, 120°C, and 130°C, and a holding time of 0.5h to 1.5h; a third calcination at a temperature of 180°C to 210°C, such as 190°C, 200°C, and 210°C, and a holding time of 2h to 4h; a fourth calcination at a temperature of 500°C to 600°C, such as 540°C, 550°C, and 560°C, and a holding time of 2h to 6h. The present invention optimizes the specific steps in the second calcination into four stages of calcination performed sequentially, which helps to achieve the segmented decomposition of the carbon source mixed with the precursor, avoiding its large-scale decomposition in a certain temperature range, generating more gas, and a large amount of other escapes causing the material volume to expand significantly, resulting in a reduced filling rate and a decrease in electrochemical performance. In addition, the segmented calcination makes the gas escape more slowly, better avoiding the formation of a large number of void structures in the obtained positive electrode material first and then rapidly shrinking, resulting in a decrease in compacted density, an increase in BET specific surface area, and deterioration of electrochemical performance.
[0060] Furthermore, in order to adapt the state of the composite material corresponding to the above-mentioned four-stage calcination process, so as to obtain a positive electrode material with excellent phase purity and crystallinity, improve its performance in sodium ion batteries, and ultimately optimize the capacity of the resulting battery, it is preferred that the heating rates of the first calcination, the second calcination, the third calcination and the fourth calcination are each independently 3°C / min to 10°C / min, such as 6°C / min, 6.5°C / min, and 7.0°C / min.
[0061] The third aspect of the present invention provides a positive electrode sheet, which includes the above-mentioned positive electrode material, or includes the positive electrode material prepared by the preparation method of the above-mentioned positive electrode material. The above-mentioned positive electrode material or the obtained above-mentioned positive electrode material has a lower powder resistivity, so that the positive electrode sheet in which it is located can have better comprehensive performance.
[0062] The fourth aspect of the present invention provides a sodium ion battery, which includes the above-mentioned positive electrode plate. Since the positive electrode material in the positive electrode plate obtained by the present invention has excellent performance, the sodium ion battery in which it is located exhibits higher energy density, higher capacity and efficiency, and also has excellent cycle stability.
[0063] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0064] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0065] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0066] 1. Preparation method
[0067] Example 1
[0068] A method for preparing a positive electrode material:
[0069] (1) Sodium bicarbonate was used as the sodium source, anhydrous ferric phosphate was used as the iron and phosphorus sources, and diammonium phosphate was used as the phosphorus source. 4.2 Fe 3.2 (PO4) 2.2 P2O7 (i.e. the molar ratio of olivine phosphate to polyanionic phosphate is 0.2:1) is added, and the sodium source is added in an excess of 5.5%, i.e. the molar ratio of sodium source: iron source: phosphorus source = 4.2:3.2:4.2, and water is used as the dispersion liquid to obtain the first slurry.
[0070] (2) The first slurry is spray-dried and subjected to a first calcination, wherein the first calcination is performed by heating from room temperature to 450° C. at a rate of 5° C. / min for 2 h, and the second calcination is performed by heating from room temperature to 600° C. at a rate of 5° C. / min for 12 h to obtain a precursor.
[0071] (3) Soluble starch, polyethylene glycol PEG-2000 and graphene are used as carbon sources, and the carbon layer content in the final positive electrode material is 3%, and the weight ratio of soluble starch, polyethylene glycol PEG-2000 and graphene is 1.4:1:0.2. The carbon source is mixed with the precursor and water is used as a dispersion liquid to prepare a second slurry.
[0072] (4) The second slurry was spray dried and subjected to a second calcination at a heating rate of 6.5° C. / min, with a total of four calcinations to obtain a positive electrode material, and the conditions were as follows:
[0073] The first stage of calcination was at 50°C and the holding time was 1.5h;
[0074] The second stage of calcination is at 120°C and the holding time is 1h;
[0075] The third stage of calcination is at 200°C and the holding time is 3h;
[0076] The fourth stage of calcination is at 550°C and the holding time is 4h.
[0077] After the second calcination, the two organic carbon sources, soluble starch and polyethylene glycol PEG-2000, in the carbon layer are transformed into an amorphous carbon part, and the inorganic carbon source graphene is transformed into an inorganic carbon part. The mass ratio of the carbon layer provided by the three is 4.5:5:0.5. That is, based on the total weight of the carbon layer being 100%, the weight of the inorganic carbon part accounts for 5.0%.
[0078] The SEM characterization results of the obtained positive electrode material are shown in Figure 1 .
[0079] The process flow of the preparation method of the positive electrode material is shown in Figure 4 .
[0080] Example 2
[0081] A method for preparing a positive electrode material:
[0082] The difference between this embodiment and embodiment 1 is that the amount of each raw material added is changed so that the molar ratio of olivine phosphate to polyanionic phosphate in the composite particles of the obtained positive electrode material is 0.3:1. The molecular formula of the obtained composite particles is Na 4.3 Fe 3.3 (PO4) 2.3 P2O7.
[0083] Example 3
[0084] A method for preparing a positive electrode material:
[0085] The difference between this embodiment and embodiment 1 is that the amount of each raw material added is changed so that the molar ratio of olivine phosphate to polyanionic phosphate in the composite particles of the obtained positive electrode material is 0.4:1. The molecular formula of the obtained composite particles is Na 4.4 Fe 3.4 (PO4) 2.4 P2O7.
[0086] Example 4
[0087] A method for preparing a positive electrode material:
[0088] The difference between this embodiment and embodiment 1 is that the amount of each raw material added is changed so that the molar ratio of olivine phosphate to polyanionic phosphate in the composite particles of the obtained positive electrode material is 0.5:1. The molecular formula of the obtained composite particles is Na 4.5 Fe3.5 (PO4) 2.5 P2O7.
[0089] Example 5
[0090] A method for preparing a positive electrode material:
[0091] The only difference between this embodiment and embodiment 1 is that the carbon source added in step (3) is such that the carbon layer content in the final positive electrode material is still 3%, and the weight ratio of soluble starch, polyethylene glycol PEG-2000 and graphene added is changed to 1.48:1:0.2.
[0092] After the second calcination, the two organic carbon sources, soluble starch and polyethylene glycol PEG-2000, in the carbon layer are transformed into an amorphous carbon part, and the inorganic carbon source graphene is transformed into an inorganic carbon part. The mass ratio of the carbon layer provided by the three is 4.75:5:0.25. That is, based on the total weight of the carbon layer being 100%, the weight of the inorganic carbon part accounts for 2.5%.
[0093] Example 6
[0094] A method for preparing a positive electrode material:
[0095] The only difference between this embodiment and embodiment 1 is that the carbon source added in step (3) is such that the carbon layer content in the final positive electrode material is still 3%, and the weight ratio of soluble starch, polyethylene glycol PEG-2000 and graphene added is changed to 1.24:1:0.4.
[0096] After the second calcination, the two organic carbon sources, soluble starch and polyethylene glycol PEG-2000, in the carbon layer are transformed into an amorphous carbon part, and the inorganic carbon source graphene is transformed into an inorganic carbon part. The mass ratio of the carbon layer provided by the three is 4:5:1. That is, based on the total weight of the carbon layer being 100%, the weight of the inorganic carbon part accounts for 10%.
[0097] Example 7
[0098] A method for preparing a positive electrode material:
[0099] The only difference between this embodiment and embodiment 1 is that the carbon source added in step (3) is used to change the carbon layer content in the final positive electrode material to 1.5%, and the carbon source only includes soluble starch and polyethylene glycol PEG-2000, and the ratio of the added amount of soluble starch to polyethylene glycol PEG-2000 is 1.56:1. The mass ratio of the carbon layers provided by the soluble starch and polyethylene glycol PEG-2000 in the obtained carbon layer is 1:1, and the inorganic carbon part is 0%.
[0100] Example 8
[0101] A method for preparing a positive electrode material:
[0102] The only difference between this embodiment and embodiment 1 is that the carbon source added in step (3) includes only soluble starch, and the carbon layer provided by the soluble starch accounts for 3% of the obtained positive electrode material.
[0103] Example 9
[0104] A method for preparing a positive electrode material:
[0105] The only difference between this embodiment and embodiment 1 is that the carbon source added in step (3) only includes polyethylene glycol PEG-2000, and the carbon layer provided by polyethylene glycol PEG-2000 accounts for 3% of the obtained positive electrode material.
[0106] Example 10
[0107] A method for preparing a positive electrode material:
[0108] The only difference between this embodiment and embodiment 1 is that the total amount of the carbon source in step (3) is changed so that the mass fraction of the carbon layer in the final positive electrode material is changed to 1%.
[0109] Embodiment 11
[0110] A method for preparing a positive electrode material:
[0111] The only difference between this embodiment and embodiment 1 is that the total amount of the carbon source in step (3) is changed so that the mass fraction of the carbon layer in the final positive electrode material is changed to 4%.
[0112] Example 12
[0113] A method for preparing a positive electrode material:
[0114] The only difference between this embodiment and embodiment 1 is that the calcination conditions in step (4) are different, specifically:
[0115] The first stage of calcination, the temperature is 30℃, the holding time is 2.5h;
[0116] The second stage of calcination, the temperature is 80℃, the holding time is 2h;
[0117] The third stage of calcination is at 240°C and the holding time is 1h;
[0118] The fourth stage of calcination is at 650°C and the holding time is 1h.
[0119] Example 13
[0120] A method for preparing a positive electrode material:
[0121] The only difference between this embodiment and embodiment 1 is that the calcination conditions in step (4) are different, specifically:
[0122] The first stage of calcination, the temperature is 70℃, the holding time is 0.5h;
[0123] The second stage of calcination, the temperature is 140℃, the holding time is 0.3h;
[0124] The third stage of calcination is at 150°C and the holding time is 5h;
[0125] The fourth stage of calcination is at 450°C and the holding time is 7h.
[0126] Embodiment 14
[0127] A method for preparing a positive electrode material:
[0128] The only difference between this embodiment and embodiment 1 is that the calcination conditions in step (4) are different, specifically:
[0129] The first stage of calcination is at 200°C and the holding time is 3h;
[0130] The second stage of calcination was carried out at a temperature of 550°C and a holding time of 4 hours.
[0131] The SEM characterization results of the obtained positive electrode material are shown in Figure 2 .
[0132] Embodiment 15
[0133] A method for preparing a positive electrode material:
[0134] The only difference between this embodiment and embodiment 1 is that the calcination conditions in step (4) are different, specifically:
[0135] Only one stage of calcination was carried out, the temperature was 550°C and the holding time was 4h.
[0136] The SEM characterization results of the obtained positive electrode material are shown in Figure 3 .
[0137] Example 16
[0138] A method for preparing a positive electrode material:
[0139] The only difference between this embodiment and embodiment 1 is that the sodium source, iron source, phosphorus source and carbon source are mixed simultaneously, water is used as a dispersant to obtain a slurry, and the positive electrode material is obtained under the drying and calcining conditions in step (2) of embodiment 1.
[0140] Embodiment 17
[0141] A method for preparing a positive electrode material:
[0142] The only difference between this embodiment and embodiment 1 is that the heating rates of the four stages of calcination in step (4) are all changed to 3°C / min.
[0143] Embodiment 18
[0144] A method for preparing a positive electrode material:
[0145] The only difference between this embodiment and embodiment 1 is that the heating rates of the four stages of calcination in step (4) are all changed to 10°C / min.
[0146] Embodiment 19
[0147] A method for preparing a positive electrode material:
[0148] The only difference between this embodiment and embodiment 1 is that the heating rates of the four stages of calcination in step (4) are all changed to 2°C / min.
[0149] Embodiment 20
[0150] A method for preparing a positive electrode material:
[0151] The only difference between this embodiment and embodiment 1 is that the heating rates of the four stages of calcination in step (4) are all changed to 12°C / min.
[0152] Embodiment 21
[0153] A method for preparing a positive electrode material:
[0154] The difference between this embodiment and embodiment 1 is that the calcination conditions in step (2) are different, specifically:
[0155] The first calcination was carried out by heating from room temperature to 350°C at a rate of 5°C / min for 3 h, and the second calcination was carried out by heating from 350°C to 500°C at a rate of 5°C / min for 11 h to obtain the precursor.
[0156] Embodiment 22
[0157] A method for preparing a positive electrode material:
[0158] The difference between this embodiment and embodiment 1 is that the calcination conditions in step (2) are different, specifically:
[0159] The first calcination was carried out by heating from room temperature to 550°C at a rate of 5°C / min for 1 hour, and the second calcination was carried out by heating from room temperature to 700°C at a rate of 5°C / min for 13 hours to obtain the precursor.
[0160] Comparative Example 1
[0161] A method for preparing a positive electrode material:
[0162] The difference between this comparative example and Example 1 is that the amount of each raw material added is changed so that the molar ratio of olivine phosphate to polyanionic phosphate in the composite particles of the obtained positive electrode material is 0:1.
[0163] Comparative Example 2
[0164] A method for preparing a positive electrode material:
[0165] The difference between this comparative example and Example 1 is that the amount of each raw material added is changed so that the molar ratio of olivine phosphate to polyanionic phosphate in the composite particles of the obtained positive electrode material is 0.1:1.
[0166] Comparative Example 3
[0167] A method for preparing a positive electrode material:
[0168] The difference between this comparative example and Example 1 is that the amount of each raw material added is changed so that the molar ratio of olivine phosphate to polyanionic phosphate in the composite particles of the obtained positive electrode material is 0.8:1.
[0169] Comparative Example 4
[0170] A method for preparing a positive electrode material:
[0171] The difference between this comparative example and Example 1 is that the amount of each raw material added is changed so that the molar ratio of olivine phosphate to polyanionic phosphate in the composite particles of the obtained positive electrode material is 1:1.
[0172] 2. Test Method
[0173] D50: GB / T 19077, particle size analysis by laser diffraction method.
[0174] BET: GB / T 19587, Determination of specific surface area of solid substances by gas adsorption BET method.
[0175] Filling rate: GB / T 5000-2017, Determination of powder filling density of powder metallurgy parts.
[0176] Compacted density: GB / T 24533, Determination of compacted density of powders.
[0177] Tap density: GB / T 5162-2021, Determination of tap density of powders.
[0178] Powder internal resistance: tested using the four-probe method at a pressure of 10 MPa.
[0179] Battery performance test:
[0180] (1) Preparation of positive electrode sheet: The positive electrode materials obtained in the examples and comparative examples were mixed with acetylene black (as a conductive agent) and polyvinylidene fluoride (PVDF, as a binder) at a mass ratio of 88:6:6, with a mass accuracy of 0.001g to form positive electrode slurry. Aluminum foil was used as the current collector for the positive electrode sheet. The positive electrode material, acetylene black, PVDF and N-methylpyrrolidone were stirred and slurried to obtain a positive electrode slurry, which was evenly coated on the aluminum foil. After drying in an oven at 100°C, it was cut into electrode sheets with a diameter of 18 mm and a thickness of 0.10 mm. The electrode sheets were weighed with a mass accuracy of 0.0001g.
[0181] (2) Battery assembly: In an inert gas glove box with water and oxygen contents ≤ 0.0005%, a sodium metal sheet was used as the negative electrode material, a polypropylene microporous film was used as the separator, and a sodium ion battery electrolyte composed of 1 mol / L sodium perchlorate (NaClO4) and a mixed carbonate-based organic solvent [ethylene carbonate (EC) / diethyl carbonate (DEC) / fluoroethylene carbonate (FEC) (the volume ratio of EC, DEC, and FEC was 1:1:0.05)] was assembled and sealed to form a test cell.
[0182] (3) Battery testing: The test battery was subjected to charge-discharge cycles at 25°C on a sodium ion battery electrochemical performance tester (Wuhan Blue Electric CT2001A battery testing system):
[0183] (a) 0.2C rate current charging, charging limit voltage 4.0V;
[0184] (b) 0.2C rate current discharge, discharge termination voltage 2.0V.
[0185] The test results are shown in Tables 1 and 2.
[0186] Table 1
[0187]
[0188]
[0189] Table 2
[0190]
[0191]
[0192] III. Analysis of test results of various embodiments and comparative examples
[0193] From the above results, it can be seen that the above embodiments of the present invention achieve the preparation of a sodium ion battery positive electrode material with excellent electrochemical performance. Specifically:
[0194] By comparing the embodiments with the comparative examples, it can be seen that the positive electrode material prepared in the present application, in which the molar ratio of olivine phosphate to polyanionic phosphate is (0.2-0.5):1, and the polyanionic phosphate phase encapsulates the nanocrystals of olivine phosphate, has more excellent performance than conventional iron-based sodium phosphate electrical materials. After being used as a positive electrode material to prepare a sodium ion battery, it exhibits higher first charge specific capacity and first discharge specific capacity.
[0195] By comparing Examples 1 to 3 with Example 4 and Comparative Examples 1 to 4, it can be seen that when the molar ratio of olivine phosphate to polyanionic phosphate is (0.2-0.5):1, especially (0.2-0.4):1, the compatibility between the two phases of olivine phosphate and polyanionic phosphate is better, and the electrochemical performance of the resulting positive electrode material is more superior.
[0196] By comparing Examples 1 to 3 with Examples 5 to 9, it can be seen that the preferred carbon layer is an amorphous carbon part formed by an organic carbon source and an inorganic carbon part formed by an inorganic carbon source, and the weight proportion of the inorganic carbon part is 2.5% to 5.0%, which is conducive to promoting the two carbon layers with different characteristics and functions to work together, and further improve the electrochemical performance of the positive electrode material. In particular, when the preferred carbon source is specifically soluble starch, polyethylene glycol and graphene, and the ratio of the addition amount of soluble starch, PEG-2000 and graphene is (1.2 to 1.5): 1: (0.2 to 0.4), more preferably (1.25 to 1.5): 1: (0.2 to 0.3), it is conducive to better synergizing the superior performance of graphene, polyethylene glycol and soluble starch after calcination, thereby obtaining a carbon layer with uniform coating and good conductivity, and improving the electrochemical performance of the obtained positive electrode material.
[0197] By comparing Examples 1 to 3 with Examples 10 and 11, it can be seen that when the mass fraction of the carbon layer is 1.5% to 3.0%, based on the total weight of the positive electrode material being 100%, the electron transport capacity and stability of the obtained positive electrode material can be better balanced, thereby improving its electrochemical performance.
[0198] By comparing Examples 1 to 3 with Example 16, it can be seen that the two-step method in the embodiments of the present application is more helpful in improving the electronic conductivity, compaction density and tap density of the obtained positive electrode material than the one-step method commonly used in the art, thereby obtaining a positive electrode material with higher electrochemical performance.
[0199] By comparing Examples 1 to 3 with Examples 21 and 22, it can be seen that in the process of forming the precursor in the first calcination process, the calcination process is controlled to be a first calcination and a second calcination in sequence, and the temperature of the first calcination is 400°C to 500°C, and the time is 1.5h to 2.5h; the temperature of the second calcination is 550°C to 650°C, and the time is 10h to 14h, which can promote the formation of a high phase purity precursor and improve the electrochemical properties of the resulting positive electrode material.
[0200] By comparing Examples 1 to 3 with Examples 12 to 15, it can be seen that in the process of forming polyanionic phosphate during the second calcination, the second calcination is optimized into four stages, and the temperature range and calcination time are precisely controlled. This can help to achieve the segmented decomposition of the carbon source mixed with the precursor, while inhibiting the degradation of the electrochemical properties of the resulting positive electrode material; it can also enable better recombination between the two crystal phases, thereby significantly improving the electrochemical properties of the resulting positive electrode material.
[0201] By comparing Examples 1 to 3 with Examples 17 to 20, it can be seen that the heating rate of 3°C / min to 10°C / min can promote the improvement of the phase purity and crystallinity of the obtained positive electrode material, thereby making it exhibit higher electrochemical performance.
[0202] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes composite particles, and the molecular formula of the composite particles is: Na x Fe y (PO4) n (P2O7) m , where x is 4.2 to 4.5, y is 3.2 to 3.5, n is 2.2 to 2.5, and m is 0.9 to 1.1; The composite particles include olivine phosphate and polyanionic phosphate coated on the surface of the olivine phosphate, and the molar ratio of the olivine phosphate to the polyanionic phosphate is (0.2-0.5):
1.
2. The positive electrode material according to claim 1, characterized in that The molar ratio of the olivine phosphate to the polyanionic phosphate is (0.2-0.4):
1.
3. The positive electrode material according to claim 1 or 2, characterized in that The positive electrode material further includes a carbon layer coated on the surface of the composite particles, and the mass fraction of the carbon layer is 1.5% to 3.0% based on the total weight of the positive electrode material as 100%; Preferably, the carbon layer is an amorphous carbon portion formed by an organic carbon source and / or an inorganic carbon portion formed by an inorganic carbon source; More preferably, the carbon layer is a combination of the amorphous carbon part and the inorganic carbon part, and based on the total weight of the carbon layer being 100%, the weight of the inorganic carbon part accounts for 2.5% to 5.0%.
4. The positive electrode material according to any one of claims 1 to 3, characterized in that The powder resistivity of the positive electrode material is 12000 Ω·cm to 93000 Ω·cm.
5. A method for preparing a positive electrode material, characterized in that: The preparation method of the positive electrode material comprises: The sodium source, the iron source and the phosphorus source are prepared into a first slurry; The first slurry is subjected to a first drying and a first calcination to obtain a precursor; preparing the precursor and the carbon source into a second slurry; The second slurry is subjected to a second drying and a second calcination to obtain the positive electrode material.
6. The method for preparing the positive electrode material according to claim 5, characterized in that: In the first slurry, the molar ratio of sodium element, iron element and phosphorus element is (4.2-4.86): (3.2-3.5): (4.2-4.5); Preferably, the first calcination comprises a first calcination and a second calcination performed sequentially, and, The first calcination temperature is 400°C to 500°C, and the time is 1.5h to 2.5h; the second calcination temperature is 550°C to 650°C, and the time is 10h to 14h; More preferably, the first calcination is performed under a protective atmosphere.
7. The method for preparing the positive electrode material according to claim 6, characterized in that: The sodium source is selected from one or more of sodium bicarbonate, sodium phosphate, sodium monohydrogen phosphate and sodium dihydrogen phosphate; the iron source is selected from one or more of anhydrous ferric phosphate, polyhydrated ferric phosphate, ferrous phosphate monohydrogen and ferrous oxalate; the phosphorus source is selected from one or more of anhydrous ferric phosphate, diammonium phosphate, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, polyhydrated ferric phosphate and ferrous oxalate; Preferably, the carbon source comprises an organic carbon source and / or an inorganic carbon source; Preferably, the organic carbon source is selected from one or more of citric acid, glucose, sucrose, soluble starch and polyethylene glycol; and / or, the inorganic carbon source is selected from one or more of graphite, carbon nanotubes and graphene; Preferably, the carbon source comprises the soluble starch, the polyethylene glycol and the graphene; More preferably, the polyethylene glycol is PEG-2000.
8. The method for preparing a positive electrode material according to any one of claims 5 to 7, characterized in that: The second calcination comprises the following steps: The first stage of calcination is at a temperature of 40°C to 60°C and the holding time is 1h to 2h; The second stage of calcination is at a temperature of 100°C to 130°C and a holding time of 0.5h to 1.5h; The third stage of calcination, the temperature is 180℃~210℃, the holding time is 2h~4h; The fourth stage of calcination is at a temperature of 500°C to 600°C and a holding time of 2h to 6h; Preferably, the heating rates of the first stage calcination, the second stage calcination, the third stage calcination and the fourth stage calcination are each independently 3° C. / min to 10° C. / min.
9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the positive electrode material according to any one of claims 1 to 4, or the positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 5 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Preparation method of sodium-ion battery cathode material as well as product and application of sodium-ion battery cathode material
CN105789617A
Carbon-cladded sodium ferric pyrophosphate material and preparation method thereof as well application of carbon-cladded sodium ferric pyrophosphate material serving as sodium-ion battery positive electrode material
CN108123129A
Novel sodium ion battery positive electrode material and preparation method thereof
CN108565418A
Preparation method of sodium ion battery positive electrode material
CN118637581A
Cited By
High-compaction-density ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN119929768A
Highly compacted density pyrophosphate sodium ferric phosphate cathode material and preparation method thereof
CN119929768B
Sodium ion battery monomer, battery device and power utilization device
CN121583995A
